Clay nanocomposites as engineered drug delivery systems. Issue 55 (20th May 2016) - Jafarbeglou, Maryam; Abdouss, Majid; Shoushtari, Ahmad Mousavi; Jafarbeglou, Majid
Abstract : Nanoclays as natural ceramics have most benefits as reservoirs for adjust drug release and decrease their overdose toxicity. Clay based nanocomposites have adequate porosity for sequencing and prolonging drug release versus their polymers only. Abstract : Clays belong to a category of silica layered ingredients that are commonly used in the pharmaceutical industry, either as ingredients or in combination in composites and hybrids. The specific structure of clay provides effective drug delivery systems with the ability to interact with drugs and to control release. Numerous research articles have been published in this respect and valuable results reported, mostly for oral routes. However, overview and discussion of the recent and rapidly growing research along with their theoretical principles are required for understanding and exploring the great potential of this method. To further this aim, we have provided an illustrated and comprehensive study from the point of view of a nanotechnologist, interested in investigating clay aggregate effects at the nano and meso scales for the development of nano-composites and hybrids accomplished with clay. In the first stage, a review of the molecular structure and physicochemical properties of clay are discussed and then we continue with a survey of clay and nanoclay origins, preparation methods, modification and incorporation as nano-hybrids, nano-composites, and nano and microfibers. Also their effects on drug overdose toxicity and on the mechanism of drug loading and release are discussed. Finally, this review summarizes further expansions of their progressive usage in biopharmaceutical applications with the help of integration of release methods and engineering of nanostructured clays in polymeric nanocomposites.